Review on Blockchain-Based Offline Payment Solutions - Lanka, Surekha; Suwannatat, Phothiwong; Pumhiran, Nalinnee (Journal of Trends in Computer Science and Smart Technology, 2026)
Blockchain technology has proven to be a revolutionary base technology for the development of digital payment systems, which include properties like decentralization, transparency, and strong cryptography. However, most existing blockchain-based payment systems require always-connected scenarios, limiting their applicability in environments where no or intermittent internet connectivity is available. Hence, there is increased research in existing studies on blockchain-based offline payment systems, particularly from the viewpoints of financial inclusion and Central Bank Digital Currencies. The objective of this paper is to carry out a detailed review of existing blockchain-based offline payment systems, which includes discussions on design, security, and assumptions. The proposed work will group the prominent existing payment systems along the lines of state channel networks, hardware-based payment systems, and offline token payment systems, which will be analyzed for their pros and cons. In addition, it also raises awareness of prominent security aspects like authentication using cryptography, trusted execution environments, and delayed reconciliation, considering this study to assume certain conditions when examining the offline environment. Finally, based on the major existing work, it will outline important research opportunities in double spending, scalability, privacy, interoperability, and usability. The purpose of this study is, through synthesis, to provide a structured view of the offline blockchain payment platform and help focus R&D efforts on effective, secure, and scalable offline digital payment systems.
Keywords: Blockchain; Offline Payment; Secure Transaction; E-Commerce; Central Bank Digital Currencies; Decentralized Architecture; Digital Wallet; Key Management; Smart Cards